Education and the Qur'an - Karasakal, Şaban (SILA SCIENCE, 2012)
This study aims to discuss the issue of education in accordance with the Qur'an. The Qur'an discusses the issue of education, from its comprehensive perspective, within the frame of knowledge and information. The Qur'an, pointing out to issues of education in the broadest terms, invites us to discover unseen meanings behind all facts. For this purpose, a lot of notions which were unimportant in the time the Qur'an was sent have gained different meanings and have been revived in this new system of values and around notions of human and education.
Keywords: Qur'an; Education; Knowledge